Demokrasi dan Partai Lokal: Mencermati Dinamika Pemilihan Umum di Aceh - Marwazi, Raja; Fatimah, Siti (Prodi Tata Negara (Siyasah) IAIN Langsa, 2023)
Democratic elections have two meanings: the success and failure of democracy. Pilkada is said to be successful because it shows community participation, the nomination process, campaigns, and political contracts. Pilkada is called a failure because it shows money practices, large numbers of abstentions, violence in elections, and ignorance of voters' political rights. The purpose of this study is to analyze democratic elections within the framework of local democracy and the journey of local parties from 2006 to 2019. This paper is a literature review (library research). Data were obtained from several empirical studies that were directly related to the problems of this research. To strengthen the data and analysis, this paper also uses important journals to enrich the findings of the data. This paper uses a legal approach (legal approach) and a historical approach (historical approach). This approach is used to look legally and historically at politics during the election process. Based on the findings of empirical data, it illustrates that in elections in Aceh, intimidation, violence, and money politics still occur; this happens almost in every district and city. This condition shows that democratic elections have not been touched on a regular basis—substantially, they have only been touched procedurally.